Bubble Curtains: Herbivore Exclusion Devices for Ecology and Restoration of Marine Ecosystems? - Bennett, Scott; Wernberg, Thomas; de Bettignies, Thibaut (Frontiers in Marine Science, 2017)
Herbivorous fishes play a critical role in maintaining or disrupting the ecological resilience of many kelp forests, coral reefs and seagrass ecosystems, worldwide. The increasing rate and scale of benthic habitat loss under global change has magnified the importance of herbivores and highlights the need to study marine herbivory at ecologically relevant scales. Currently, underwater herbivore exclusions (or inclusions) have been restricted to small scale experimental plots, in large part due to the challenges of designing structures that can withstand the physical forces of waves and currents, without drastically altering the physical environment inside the exclusion area. We tested the ability of bubble curtains to deter herbivorous fishes from feeding on seaweeds as an alternative to the use of rigid exclusion cages. Kelps (Ecklonia radiata) were transplanted onto reefs with high browsing herbivore pressure into either unprotected plots, exclusion cages or plots protected by bubble curtains of 0.785 m2 and 3.14 m2. Remote underwater video was used to compare the behavioural response of fishes to kelps protected and unprotected by bubble curtains. Kelp biomass loss was significantly lower inside the bubble curtains compared to unprotected kelps and did not differ from kelp loss rates in traditional exclusion cages. Consistent with this finding, no herbivorous fishes were observed entering into the bubble curtain at any point during the experiment. In contrast, fish bite rates on unprotected kelps were 1621 ± 702 bites hr-1 (mean ± SE). Our study provides initial evidence that bubble curtains can exclude herbivorous fishes, paving the way for future studies to examine their application at larger spatial and temporal scales, beyond what has been previously feasible using traditional exclusion cages.